Tourism development and economic growth : Evidence from developed countries / Noorsyahira Zakaria - Zakaria, Noorsyahira (Universiti Teknologi Mara Perlis, 2020)
The aim of this study is to investigate the effects of tourism development on economic growth. The dependent variable for this study is economic growth and independent variables are tourism receipts, foreign direct investment, inflation and labour force. This study utilized panel data from 20 selected developed countries ranging from 2005 to 2017. Result from regression analysis shows that tourism receipts, foreign direct investment and labour force are statistically significant in effecting economic growth. The findings from causality analysis stated that there is a unidirectional effect between GDP and TER with labour force.